Robot‐assisted laparoscopic augmentation ileocystoplasty and Mitrofanoff appendicovesicostomy in children: Step‐by‐step and modifications to UChicago technique. Issue 1 (20th March 2020) - Adamic, Brittany; Kirkire, Lakshmi; Andolfi, Ciro; Labbate, Craig; Aizen, Joshua; Gundeti, Mohan
Abstract: Objective: To describe the step‐by‐step techniques and modifications for robot‐assisted augmentation ileocystoplasty and Mitrofanoff appendicovesicostomy in a pediatric population with updated institutional results. Introduction: Robot‐assisted laparoscopic augmentation ileocystoplasty with Mitrofanoff appendicovesicostomy (RALIMA) protects the upper urinary tract and reestablishes continence in patients with refractory neurogenic bladder. Robotic assistance could provide the benefits of minimally invasive surgery without the challenges of pure laparoscopy. Here, we focus on the outcomes of RALIMA with salient tips and modifications of the technique. Methods: We performed a retrospective review of our robotic database and identified 24 patients who underwent attempted robot‐assisted laparoscopic augmentation ileocystoplasty (RALI) between 2008 and 2017 by a single surgeon at an academic center. Outcomes of interest included operative time, hospitalization time, postoperative complications, and change in bladder capacity. RALI and all concomitant procedures were performed using the da Vinci® surgical system (Intuitive Surgical, Sunnyvale, CA, USA). Results: Of 24 patients, 20 successfully underwent RALI. Eighty percent underwent concomitant appendicovesicostomy (APV), 40% underwent antegrade continence enema channel formation (ACE), and 30% underwent a bladder neck procedure. Mean operative time was 573 minutes and the most recent RALIMA was 360 minutes. The average return to regular diet was 3.9 days and length of stay was 6.9 days. Mean change in bladder capacity was 244% postoperatively. Thirty‐day complications were noted in 35% of patients; one Clavian grade I (5%) complication, five grade II (25%) complications, and one grade IIIb (5%) complication. With a median follow‐up of 83.1 months we note a 25% incidence of bladder stones, 15% upper tract stones, 5% incidence of bladder rupture, and 5% small bowel obstruction. No patients required re‐augmentation in the follow‐up period. Conclusions: RALI has similar functional outcomes and complications when compared with the open augmentation ileocystoplasty literature. RALI is desirable due to favorable pain control with decreased length of stay. Long‐term outcomes after RALI are similar to the open approach. As the operative time is currently the largest point of criticism with the robotic approach, we discuss modifications to decrease the operative time.